Epidemiological factors in patients with larynx cancer treated by surgery, radiotherapy or therapeutic associations - Gustavo Henrique Barbosa Nunes Da Silva; Michelle Gomes Miranda; Débora Souza Rodrigues; Geralda Rodrigues De Souza; Christiana Vargas Ribeiro (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2019)
The aim of this research was to analyze the influence of epidemiological factors in patients with laryngeal carcinoma treated by surgery, radiotherapy or therapeutic associations. A quantitative retrospective analysis was performed, based on a master's thesis, of 34 individuals with this pathology, taking into consideration: gender, age, life habits and type of treatment. These factors were associated with the projections of the number of new cases, starting in 2018, according to INCA and IARC data. Due to lifestyle, men are more likely to get laryngeal cancer, and the association of alcohol and tobacco increases the chance and degree of manifestation of this carcinoma. In relation to age, the age group between 55 and 69 years is the most affected. The most indicated treatment is radiotherapy due to the low rate of serious complications, with minimal effect on the patient's life, which does not need hospitalization; besides being a non-invasive, extremely precise technique used in tumors that need a great accuracy, which allows the elimination of the tumor, preserving the structure and functionality of the larynx.